O ensino da literatura em Roraima : da gênese da Universidade Federal de Roraima aos dias atuais - Mibielli, Roberto (2007)
This work was intended to interpret the literary canon as it is taught at Universidade Federal de Roraima UFRR. The analysis was developed mainly through the bibliography and the content of the courses of Literature there, from the very foundation of that University to 2003. There is also a comparison between the academic canon of UFRR, UFC and UFF and we tackle the issue of teaching literature in Roraima, with the specific problems raised by a very peculiar situation there. We started from the hypothesis that the disciplinary model in UFRR was derived from the model of UFC, since a relevant group of professors came from that University (or were students there) to Roraima at the very beginning of the courses in UFRR. As a third comparative level, we included UFF, focusing on Brazilian Literature, Portuguese Literature and Theory of Literature. 50 comparative charts were made, and their analysis led to the following conclusions: 1) UFRR´s canon is not a straightforward imitation of UFC, because there were relevant changes to be considered; 2) there were important disciplinary alterations in all the Universities encompassed by our work; 3) UFRR has more panoramic and historically oriented disciplines; 4) it is necessary to raise a consciousness that local literature must be taken into account at UFRR if we aim to have the recognition of a local literary production and canon in the future there.